Pemanfaatan Energi Terbarukan untuk Pembangkit Listrik Tenaga Surya Berbasis Komunitas: Menuju Desa Mandiri Energi - Elvira Sukma Wahyuni; Husein Mubarok; Firmansyah Nur Budiman; Setyawan Wahyu Pratomo (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2020)
Located on the equator, Indonesia is blessed with abundant sunlight. With current advances in solar cell and photovoltaic technology, sunlight can be exploited on a large scale, among other things, to be converted into electricity. This paper reports the results of the community service with a focus on the energy sector that took place in Wonosalam Hamlet. The method used was Community Based Research (BCR), where there are three stages of service, namely providing education to the local community about the benefits of sunlight and its use using photovoltaic, photovoltaic installation, and a feasibility study. The results show that with the current usage pattern, a dedication project of IDR 10,000,000 can save energy by 0.48 kWh / day, which is equivalent to around IDR 258,241.28 / year. In addition to the economic benefits that may not bring significant benefits, the broader impact of this project is expected to have an impact on how local people view the use of solar energy as an alternative energy source.